Suitability of lemon balm (Melissa officinalis L.) extract rich in rosmarinic acid as a potential enhancer of functional properties in cupcakes - Caleja, Cristina (2018)
Melissa officinalis (lemon balm) and its extracts have been frequently reported as possessing bioactive properties, offering the potential for use in development/enrichment of food products with additional functional capabilities, providing health benefits to consumers. The antioxidant, antibacterial and antifungal activity of lemon balm extract, as well as its potential hepatotoxicity were thoroughly evaluated. The extracts were then incorporated into cupcakes and their preserving effect, chemical composition, colour parameters and antioxidant activity were compared with those provided by potassium sorbate. In general, the variables with the largest differences among different storage times were energy level, sucrose, glucose, palmitic acid (C6:0) and oleic acid (C18:1n9). On the other hand, L ∗ (top), a ∗ (top), b ∗ (top), pH, capric acid (C10:0) and lauric acid (C12:0) showed the greatest variation according to cupcake formulation. The results observed indicate that the lemon balm extract rich in rosmarinic acid can provide advantageous functional properties to bakery products.